The role of pulmonary vascular endothelium in chronic obstructive pulmonary disease (COPD): Does endothelium play a role in the onset and progression of COPD? - Silvia Siragusa; Giulia Natali; Antonella Maria Nogara; Marcello Trevisani; Costanza Anna Maria Lagrasta; Silvia Pontis (Exploration of Medicine, 2023)
Chronic obstructive pulmonary disease (COPD) is an inflammatory lung pathology characterized by persistent airflow limitation and is the third leading cause of death globally. COPD pathophysiology includes both environmental and host risk factors and the presence of comorbidities contributes to its harmful outcome. Cardiovascular disease (CVD) is closely related to COPD and their coexistence is associated with worse outcomes than either condition alone. COPD impairs the cardiovascular system favoring mostly endothelial dysfunction that is a significant COPD prognostic factor at different stages of the disease. The mechanisms promoting endothelial dysfunction in the systemic and/or pulmonary circulation of COPD patients are different and include systemic inflammation, alteration of adhesion and pro-inflammatory molecules, oxidative stress, cellular senescence, and apoptosis. Nevertheless, the role of endothelium in the onset and progression of COPD and CVD is not yet fully understood. Hence, the purpose of this narrative review is to analyze the literature and provide evidence supporting the importance of endothelial dysfunction in COPD.